The relationship between physical activity and emotional status of pre-school children during school hour - Yaacob, Khairun Shahira Mat (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2016)
Physical activity brings a lot of health benefits for all including children. Several chronic diseases such as diabetes mellitus, obesity, coronary heart disease (CHD) and hypertension can be avoided by doing regular exercise along with healthy diet. Physically active lifestyle during childhood and adolescence may contribute to the lower risk of having health problems during adulthood. 60 minutes of moderate to vigorous intensity physical activity daily recommended by World Health Organization (WHO) will improve children's cardiorespiratory and muscular fitness. Physical activity is essential for pre-school children for obesity prevention and to increase gross motor, fine motor, cognitive and socialemotional skills. This study aimed to determine the relationship between physical activity level and emotional status of pre-school children during school hour. Thus, pre-school students (n=33), (18 boys and 15 girls) aged 4 to 6 years old were recruited in this study. Parameter measured to determine physical activity level was steps count (weekdays only) using accelerometer GTX3+. As for the emotional status measurement, scores from the questionnaires; "Borang Soal Selidik Tingkah Laku Kanak-kanak" was used. Based on the result, the total step counts per week spent by the pre-school children were 10784 ± 3487. Sedentary activity was found as the most activity (723 ± 161) the children spent during school hour compared to the moderate activity (375 ± 119), light activity (266 ± 59), vigorous activity (4 ± 6) and very vigorous activity. Result found a significant difference of total steps count per week between boys and girls with p< 0.05. As for the types of activity, there was no significant difference of sedentary activity (p=0.646), light activity (p=0.126), vigorous activity (p=0.054) and very vigorous activity (p=0.533) between boys and girls. Scores from the questionnaires showed that all the children involved in this study has good emotional status with the score of ( 44.30 ±2.82). However, as comparison between genders was made, it showed that girls have better emotional status compared to boys. When mean of an emotional status between ages was compared, four years old children had the most stable emotional status followed by the six and five years old children. As for the relationship between physical activity and emotional status, we found that there was no significant correlation between them (p= 0.200, r= -0.229).